Hybrid nanozyme-enhanced adaptive glycopeptide hydrogel dressing and preparation method and application thereof

CN122998458APending Publication Date: 2026-10-30QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611523989.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]本发明的目的在于提供一种杂合纳米酶增强的自适应糖肽水凝胶敷料及其制备方法与应用,以解决现有糖尿病慢性创面敷料在高糖、细菌感染、氧化应激、慢性炎症及血管生成受损等复杂病理微环境下功能单一、微环境调控能力不足、活性组分易失活或释放不可控,以及难以兼顾局部贴附、力学稳定性和组织再生促进作用等技术问题

Benefits of technology

其一,通过动态席夫碱键、氢键及金属配位共同构建稳定三维水凝胶网络,使MnS@ZGF Gel兼具可注射性、组织黏附性、自修复性、力学稳定性及可控降解性,能够适应糖尿病慢性创面的复杂病理环境;其二,MnS@ZG杂合纳米酶可在高糖条件下响应性激活,驱动葡萄糖耗竭介导的 ROS-H2S 级联信号,实现局部降糖、广谱抗菌、抗氧化、抗炎及免疫调控的协同作用;其三,该敷料能够有效促进巨噬细胞向 M2 型极化,增强血管新生、胶原有序沉积及组织重塑,从而显著加速糖尿病小鼠慢性创面闭合并减轻瘢痕形成;其四,该材料具有良好的生物相容性和体内安全性,为糖尿病慢性创面,尤其是感染性糖尿病创面的多阶段协同修复提供了一种安全、高效的多功能生物材料体系。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a hybrid nanoscale enzyme enhanced adaptive glycopeptide hydrogel dressing (MnS@ZGF Gel) and a preparation method and application thereof. A hybrid nanoscale enzyme (MnS@ZG) is constructed with manganese sulfide (MnS) as a core and Co 2+ / 2-methylimidazole / glucose oxidase as a shell, and the hybrid nanoscale enzyme is embedded in a glycopeptide network formed by self-assembly of oxidized sodium alginate, epsilon-polylysine and a temperature-sensitive F127, to obtain the MnS@ZGF Gel. The obtained hydrogel has the properties of injectability, wet-state adhesion, self-repair and mechanical stability, can drive a ROS-H2S cascade signal through glucose depletion, realizes early antibacterial and subsequent anti-inflammatory and antioxidant effects, promotes angiogenesis and regulates M2 polarization of macrophages, and further promotes collagen ordered remodeling and wound repair. The dressing has good biocompatibility and in-vivo degradability, can significantly promote healing of a diabetic chronic wound and reduce scar formation, and provides a new biomaterial system for repair of an infected diabetic chronic wound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical biomaterials technology, specifically relating to a hybrid nanozyme-enhanced adaptive glycopeptide hydrogel dressing, its preparation method, and its application in the repair of diabetic wounds. Background Technology

[0002] Diabetes mellitus is a prevalent chronic metabolic disease with numerous and serious complications. Among these, chronic diabetic wounds are one of the most common and difficult-to-treat complications, including diabetic foot ulcers, chronic lower extremity ulcers, and postoperative wounds that are difficult to heal. Because patients are in a state of chronic hyperglycemia, the wound site is often accompanied by complex pathological changes such as persistent infection, excessive activation of oxidative stress, chronic inflammatory imbalance, impaired angiogenesis, and abnormal extracellular matrix remodeling. This causes the wound to remain in the inflammatory phase for a long time, making it difficult to smoothly enter the proliferation and remodeling stages. In severe cases, it can even lead to tissue necrosis, amputation, and other adverse consequences, significantly impacting the patient's quality of life and medical burden.

[0003] Currently, traditional clinical treatments for chronic diabetic wounds mainly include debridement, anti-infection therapy, hypoglycemic drug intervention, and routine dressing. However, these methods often only provide symptomatic relief or short-term intervention and are frequently limited by issues such as blood glucose fluctuations, multidrug-resistant bacterial infections, and adverse drug reactions. They are unable to fundamentally improve the complex pathological microenvironment of the wound, which involves the coexistence of high glucose, infection, and oxidative stress. Therefore, there is an urgent need to develop a novel wound repair system that can simultaneously regulate high glucose, infection, and oxidative stress and provide extracellular matrix-like microenvironment support to meet the clinical needs for efficient repair of chronic diabetic wounds.

[0004] In recent years, glycopeptide hydrogels have attracted widespread attention in wound repair due to their combination of polysaccharide and peptide components, excellent biocompatibility, extracellular matrix-like structure, and regulated bioactivity. These materials not only provide a supportive microenvironment for cell adhesion, migration, and proliferation, but can also introduce certain immunomodulatory and pro-repair functions through structural design. Glycopeptide hydrogels, especially those derived from natural polysaccharides and bioactive peptides, exhibit significant advantages in biosafety, biodegradability, and tissue compatibility. However, existing glycopeptide hydrogels still lack the ability to precisely, adaptively, and stage-wise regulate the wound microenvironment when dealing with the complex pathological environment of diabetic wounds, such as high glucose fluctuations, persistent infection, and oxidative stress, making it difficult to achieve continuous intervention from early antibacterial and anti-inflammatory treatment to later tissue regeneration.

[0005] To enhance the functionality of hydrogel dressings, researchers have attempted to introduce metal ions, nanoparticles, enzymes, and other active molecules into the matrix to improve their antibacterial, antioxidant, angiogenesis-promoting, or blood glucose-lowering properties. For example, glucose oxidase can catalyze glucose consumption, thereby alleviating local hyperglycemia; metal-based nanomaterials can regulate reactive oxygen species levels through enzyme-like catalytic reactions; and hydrogen sulfide (H2S), a gaseous signaling molecule, has anti-inflammatory, antioxidant, and angiogenesis-promoting effects, which are beneficial for late-stage wound repair. However, the application of existing exogenous active components in hydrogels still faces many challenges, such as insufficient compatibility with the matrix, uneven dispersion, weak interfacial bonding, easy leakage of functional components, easy attenuation of catalytic activity, and difficulty in achieving a time-sequential release that matches the wound repair process, thus limiting their practical application.

[0006] Hybrid nanozymes, as a novel multi-component functional nanoplatform, are synergistically constructed from metal ions, ligands, biomolecules, and nanoparticles, exhibiting both structural designability and functional diversity. They show promising application prospects in antibacterial, redox regulation, immune modulation, and tissue regeneration. Combining them with adaptive glycopeptide hydrogels holds promise for constructing an integrated wound repair system that combines local adhesion, stable support, and multi-target microenvironment regulation. However, current research on diabetic chronic wounds lacks a multifunctional glycopeptide hydrogel dressing that can simultaneously achieve high glucose response, early antibacterial activity, late-stage anti-inflammatory and antioxidant effects, promote macrophage M2 polarization, promote angiogenesis and orderly collagen remodeling, while also possessing good injectability, tissue adhesion, self-healing properties, and biocompatibility.

[0007] Therefore, developing a hybrid nanozyme-enhanced adaptive glycopeptide hydrogel dressing that can stably adhere to the complex microenvironment of diabetic chronic wounds, exert a continuous effect, and achieve phased dynamic regulation has become a key technical problem urgently needing to be solved in the field of diabetic chronic wound repair. This invention addresses the technical bottlenecks of existing wound dressings, such as limited functionality, insufficient microenvironment regulation capabilities, and poor synergy between active components and the hydrogel matrix. It proposes to organically combine hybrid nanozymes with an adaptive glycopeptide hydrogel network to construct a multifunctional integrated wound dressing with local hypoglycemic, antibacterial, antioxidant, anti-inflammatory, macrophage M2 polarization-promoting, angiogenesis-promoting, and collagen remodeling-promoting functions, thereby meeting the urgent clinical demand for efficient, safe, and intelligent diabetic chronic wound repair materials. Summary of the Invention

[0008] The purpose of this invention is to provide a hybrid nanozyme-enhanced adaptive glycopeptide hydrogel dressing, its preparation method, and its application, in order to solve the technical problems of existing diabetic chronic wound dressings, such as limited functionality, insufficient microenvironment regulation ability, easy inactivation or uncontrollable release of active components, and difficulty in simultaneously achieving local adhesion, mechanical stability, and tissue regeneration promotion effects in complex pathological microenvironments such as high sugar, bacterial infection, oxidative stress, chronic inflammation, and impaired angiogenesis.

[0009] The objective of this invention is achieved through the following technical solution: using MnS as the core and Co... 2+ A hybrid nanozyme (MnS@ZG) was constructed using 2-methylimidazole (2-MIM) and glucose oxidase (GOD) as the shell. This nanozyme was then introduced into a glycopeptide hydrogel network composed of sodium alginate (OSA), ε-polylysine (PL), and thermosensitive F127. Through multiple interactions such as dynamic Schiff base bonds, hydrogen bonds, and metal coordination, the nanozyme-enhanced adaptive glycopeptide hydrogel dressing (MnS@ZGF Gel) was formed.

[0010] Among them, the GOD in the MnS@ZG hybrid nanozyme can catalyze the oxidation of glucose to gluconic acid and H2O2, thereby enabling the formation of MnS@ZG hybrid nanozymes. 2+ and Co 2+ It participates in triggering a Fenton-like reaction, amplifying the level of reactive oxygen species (ROS) to achieve a highly efficient antibacterial effect in the early stage of wound healing; as the local acidification increases, the core MnS further releases H2S, thereby playing an anti-inflammatory, antioxidant, angiogenesis-promoting and immunomodulatory role in the later stage of wound healing, forming a cascade regulatory mechanism of early ROS sterilization and later H2S promoting repair.

[0011] The MnS@ZGF Gel provided by this invention has good fluidity and injectability at low temperatures, can quickly gel in situ at body temperature, can adhere tightly to irregular wound surfaces, and has good mechanical stability, self-healing ability and controllable degradation properties. It can be used as a local repair dressing for diabetic chronic wounds to continuously exert a therapeutic effect.

[0012] The MnS@ZGF Gel provided by this invention exhibits significant antibacterial activity. PL can impart certain endogenous antibacterial properties to the hydrogel matrix. Further introduction of MnS@ZG hybrid nanozymes can enhance the antibacterial activity through GOD-mediated glucose oxidation and ROS amplification. Plate culture results show that, in the presence of glucose, MnS@ZGFGel significantly inhibits both Staphylococcus aureus and Escherichia coli, with a bactericidal rate approaching 99%, thereby reducing the early bacterial load in infectious diabetic wounds.

[0013] The MnS@ZGF Gel provided by this invention exhibits good cell compatibility and cell migration promotion capabilities. Scratch experiments using human umbilical vein endothelial cells as a model showed that cell migration was significantly accelerated after treatment with MnS@ZGF Gel, exhibiting a high migration rate after 24 hours of culture. This indicates that the hydrogel can promote endothelial cell migration, providing favorable conditions for wound angiogenesis and tissue regeneration.

[0014] The MnS@ZGF Gel provided by this invention has antioxidant and cytoprotective effects. In an H2O2-induced oxidative stress model, MnS@ZGF Gel significantly reduced intracellular ROS levels in L929 cells, alleviated oxidative stress-induced cell damage, and improved cell viability, indicating that it can further regulate excessive oxidative stress in the wound after infection control, providing a suitable redox microenvironment for subsequent tissue repair.

[0015] The MnS@ZGF Gel provided by this invention has anti-inflammatory and immunomodulatory effects. The released H2S can participate in regulating the inflammatory phenotype of macrophages; RAW264.7 macrophage experiments showed that after treatment with MnS@ZGF Gel, the expression of CD86, a marker of M1 macrophages, decreased, while the expression of CD206, a marker of M2 macrophages, increased. This indicates that the material can inhibit the pro-inflammatory macrophage phenotype and promote the polarization of reparative macrophages, thereby facilitating the resolution of chronic inflammation and the formation of a regenerative immune microenvironment.

[0016] The MnS@ZGF Gel provided by this invention also exhibits excellent hemostatic properties. In vitro whole blood coagulation experiments show that this hydrogel can reduce the blood coagulation index; in an SD rat liver hemorrhage model, MnS@ZGF Gel can significantly reduce bleeding. Its hemostatic effect is mainly due to the hydrogel's rapid adhesion to tissue surfaces, wound closure, and the local enrichment of blood and coagulation components by its porous network. Therefore, it can further meet the needs of wound dressings for rapid closure and early hemostasis.

[0017] This invention further provides the application of the MnS@ZGF Gel in the preparation of materials for repairing chronic diabetic wounds, especially infected diabetic wounds. Animal experiments show that this hydrogel can significantly promote the closure of infected diabetic wounds, with a wound closure rate exceeding 90% on day 14, significantly higher than the PBS control group, demonstrating excellent wound repair effects.

[0018] The MnS@ZGF Gel provided by this invention can achieve phased synergistic repair of infectious diabetic wounds. It controls infection by reducing bacterial load in the early stage, then inhibits the expression of inflammatory factors and promotes macrophage polarization to a repair phenotype, while enhancing angiogenesis, re-epithelialization and orderly collagen deposition, ultimately promoting extracellular matrix remodeling and wound tissue structure recovery.

[0019] This invention establishes a multi-stage synergistic regulatory process by combining glucose-responsive hybrid nanozymes with dynamic adaptive glycopeptide hydrogels, encompassing "local high glucose consumption - early ROS antibacterial - acidification-induced H2S release - antioxidant / anti-inflammatory and immune regulation - angiogenesis and extracellular matrix remodeling". This allows the therapeutic function to better match the different repair stages of diabetic infected wounds, from infection control and inflammation resolution to tissue regeneration and remodeling. Beneficial effects

[0020] Compared with the prior art, the hybrid nanozyme-enhanced adaptive glycopeptide hydrogel dressing provided by the present invention has the following beneficial effects: First, the stable three-dimensional hydrogel network constructed through dynamic Schiff base bonds, hydrogen bonds, and metal coordination gives MnS@ZGF Gel injectability, tissue adhesion, self-healing properties, mechanical stability, and controllable degradation, enabling it to adapt to the complex pathological environment of diabetic chronic wounds. Second, the MnS@ZG hybrid nanozyme can be responsively activated under high glucose conditions, driving glucose depletion-mediated ROS-H2S cascade signals to achieve synergistic effects of local hypoglycemia, broad-spectrum antibacterial activity, antioxidant activity, anti-inflammatory activity, and immunomodulation. Third, this dressing can effectively promote macrophage polarization towards the M2 type, enhance angiogenesis, orderly collagen deposition, and tissue remodeling, thereby significantly accelerating the closure of chronic wounds in diabetic mice and reducing scar formation. Fourth, this material has good biocompatibility and in vivo safety, providing a safe and efficient multifunctional biomaterial system for the multi-stage synergistic repair of diabetic chronic wounds, especially infectious diabetic wounds. Attached Figure Description

[0021] Figure 1Figures showing the preparation and characterization results of MnS@ZG hybrid nanozyme particles. (a) Transmission electron microscopy images of MnS, MnS@Z, and MnS@ZG nanoparticles; (b) HAADF-STEM images and elemental distribution maps of C, N, O, S, Mn, and Co for MnS@ZG nanoparticles; (c) UV-Vis absorption spectra of different systems in PBS buffer; (d) X-ray diffraction patterns of the nanoparticles; (e) H2O2 generation after 6 h of treatment with different concentrations of glucose; (f) pH change curves of MnS@ZG nanoparticle solutions containing 0, 5, and 15 mM glucose over 6 h; (g) UV-Vis absorption spectra of different systems after incubation with TMB probes in PBS buffer; the incubation time was 10 min and the pH was 5.5; (h) H2S release curves of MnS@ZG nanoparticles under different conditions.

[0022] Figure 2 Figures showing the preparation and characterization results of MnS@ZGF Gel. (a) Macroscopic image of the FOP Gel formation process; (b) Macroscopic image of the MnS@ZGF Gel formation process; (c) Macroscopic image of the injectability of MnS@ZGF Gel; (d) Scanning electron microscope image of the lyophilized hydrogel; (e) Scanning electron microscope image of the surface and internal structure of MnS@ZGF Gel, where blue circles indicate embedded nanoparticles; (f) Physical images of the adhesion performance of MnS@ZGF Gel on different substrate surfaces; (g) Adhesion strength of different hydrogels on pigskin surface at 33℃ and 60% relative humidity; (h) Frequency scan curves of different hydrogels; (i) Self-healing performance of MnS@ZGF Gel characterized by alternating high and low strain cycles. * P <0.05,** P <0.01.

[0023] Figure 3Results of MnS@ZGF Gel in promoting cell migration, in vivo degradation, antibacterial activity, and hemostatic properties. (a) Representative images of cell scratch assays at 0 h, 12 h, and 24 h under different treatment conditions; (b) Quantitative analysis results of cell migration rate; (c) In vivo fluorescence imaging of IR820-labeled MnS@ZGF Gel at different time points after subcutaneous injection in SD rats; (d) Colony growth of Staphylococcus aureus and Escherichia coli on Luria-Bertani (LB) agar plates after different hydrogel treatments; (e) In vitro whole blood coagulation evaluation results of PBS (control group), FOP Gel, and MnS@ZGF Gel; (f) Representative photographs of the blank control group and the MnS@ZGF Gel-treated group in the liver hemostasis experiment of SD rats. * P <0.05,** P <0.01.

[0024] Figure 4 The results of MnS@ZGF Gel in scavenging intracellular reactive oxygen species, evaluating its gas production performance, and regulating macrophage polarization. (a) Fluorescent images of the DCFH-DA probe in L929 cells under different treatment conditions; (b) Flow cytometry analysis results of reactive oxygen species levels in L929 cells stained with DCFH-DA after different treatments; (c) Relative cell viability of L929 cells after co-culturing with different hydrogels under H2O2 stimulation for 24 h; (d) Quantitative analysis results of expression levels of M1 macrophage marker CD86 and M2 macrophage marker CD206 using ImageJ based on Figure (f); (e) Detection results of H2S levels in RAW264.7 cells after treatment with LPS, LPS+NaHS or LPS+hydrogel extract; (f) Immunofluorescence images of CD206 (M2 macrophage marker, green) and CD86 (M1 macrophage marker, red) in RAW264.7 cells after 24 h of different treatments.

[0025] Figure 5In vivo therapeutic effects of MnS@ZGF Gel on diabetic wound healing. (a) Schematic diagram of treatment regimens for diabetic wounds using different formulations; (b) Representative images of wounds in mice in the PBS group (control group), Hydrosorb group, FG Gel group, FOP Gel group, MnS@ZF Gel group, and MnS@ZGF Gel group within 14 days of treatment; (c) Quantitative analysis results of wound closure rate in each group; (d) Body weight change curves of mice in each group during the 14-day treatment period; (e) Results of bacterial colony formation experiment in wound exudate on day 3 after treatment and Gram-stained tissue sections of wound tissue. Data are expressed as mean ± standard deviation, * P <0.05,** P <0.01.

[0026] Figure 6 Histological staining analysis results of wound tissue during wound healing. (a) Representative images of H&E staining and Masson trichrome staining of wound tissue in different treatment groups on day 7 post-treatment; (b) Representative images of IL-6 immunohistochemical staining and CD206 / CD86 immunofluorescence staining of wound tissue on day 7 post-treatment; (c) Representative images of CD31 immunofluorescence staining of wound tissue in each group on day 7 post-treatment, where red areas represent blood vessels. Detailed Implementation

[0027] Example 1: Preparation and Characterization of MnS@ZG Hybrid Nanozymes This invention provides a method for preparing MnS@ZG hybrid nanozymes through examples. S1: Weigh 0.245 g of manganese acetate tetrahydrate, 0.2 g of polyvinylpyrrolidone, and 0.016 g of sulfur powder, dissolve them separately in 5 mL of ethylene glycol, mix them, and transfer the mixture to a 50 mL three-necked flask. Sonicate for 15 min and stir magnetically for 30 min. Then, heat the mixture to 190 °C at 3 °C / min and react for 4 h. After naturally cooling to room temperature, centrifuge to collect the precipitate. Wash with carbon disulfide and anhydrous ethanol, and redisperse in 12 mL of anhydrous ethanol to obtain MnS nanoparticles.

[0028] S2: After centrifuging 1 mL of MnS dispersion, redisperse it in 2 mL of methanol solution containing 100 mg of polyvinylpyrrolidone. Sonicate for 3 min, then stir at room temperature for 4 h. Centrifuge and wash the resulting product, then redisperse it in 1 mL of methanol. Add 2 mL of 2-methylimidazolium methanol solution and 2 mL of cobalt nitrate hexahydrate methanol solution sequentially, and react at room temperature for 2 h. Repeat the above coating step once. After centrifugation and washing, MnS@Z nanoparticles are obtained.

[0029] S3: Weigh 1 mg of GOD and dissolve it in 2 mL of deionized water, and stir for 30 min; take 1 mL of MnS@Z dispersion, centrifuge and redisperse it in 2 mL of methanol / deionized water mixed solution, add it dropwise to glucose oxidase solution, stir at room temperature for 1 h, and after centrifugation and washing with deionized water, obtain MnS@ZG hybrid nanozyme particles.

[0030] The morphologies of MnS, MnS@Z, and MnS@ZG were characterized using transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Figure 1 As shown in a, MnS, MnS@Z, and MnS@ZG all exhibit uniform and regular morphologies with good dispersibility. This is further supported by the GOD characteristic absorption peaks appearing in the UV-Vis absorption spectra. Figure 1 c), indicating that GOD has been successfully integrated into the nanosystem. Elemental distribution analysis results show ( Figure 1 (b) C, N, O, S, Mn, and Co elements are uniformly distributed in MnS@ZG. XRD results show that ( Figure 1 d) MnS@ZG still retains the characteristic diffraction peaks of MnS and ZIF-67, indicating that its crystal structure is stable. Enzyme activity experiments show that ( Figure 1 MnS@ZG can catalyze the generation of H2O2 in the presence of glucose and further amplify the ROS signal. At the same time, it continuously releases H2S under acidic conditions, indicating that it has good cascade catalytic activity and acid response performance.

[0031] Example 2: Preparation and Characterization of MnS@ZGF Gel This embodiment provides a method for preparing MnS@ZGF Gel and its control hydrogel. S1: Weigh 1 g of sodium alginate (SA) and disperse it in 50 mL of deionized water. Then add 20 mL of an aqueous solution containing 3 g of sodium periodate (NaIO4). Stir the mixture at room temperature in the dark for 16 h. After the reaction is complete, add 3 mL of ethylene glycol to terminate the reaction and continue stirring for 2 h. The resulting reaction solution is purified by dialysis for 3 days and then freeze-dried to obtain oxidized sodium alginate (OSA) powder.

[0032] S2: Dissolve 0.4 g F127 in 1.2 mL PBS containing MnS@ZG nanoparticle dispersion and incubate at 4 °C for 6 h to obtain a homogeneous and transparent solution; at the same time, weigh 200 mg OSA and 200 mg ε-polylysine (PL) and dissolve each in 1 mL PBS.

[0033] S3: At 4℃, 0.4 mL of OSA solution and 0.4 mL of PL solution were added dropwise to the above F127 solution containing MnS@ZG. After thorough mixing, the mixture was incubated with gentle shaking at 37℃ for 1 h to form a hybrid nanozyme-enhanced adaptive glycopeptide hydrogel dressing, denoted as MnS@ZGF Gel.

[0034] S4: Using the same preparation method as steps S2-S3, FOP Gel was prepared by replacing the MnS@ZG nanoparticle dispersion with pure PBS, and MnS@ZFGel was prepared by replacing the MnS@ZG nanoparticle dispersion with MnS@Z nanoparticle dispersion; at the same time, a blank hydrogel, denoted as FGGel, was prepared according to the same steps without adding OSA, nanoparticles and PL.

[0035] In addition, such as Figure 2 As shown in Figure ac, the resulting hydrogel exhibits good flowability at low temperatures, while rapidly undergoing a sol-gel transition at 37 °C, indicating that MnS@ZGF Gel possesses excellent thermosensitive gelation properties and injectability. SEM results show ( Figure 2 d) All hydrogels exhibited interconnected three-dimensional porous structures, and MnS@ZG was uniformly dispersed in the hydrogel matrix, indicating that the hybrid nanozyme had been successfully embedded in the glycopeptide network. Adhesion performance tests showed that ( Figure 2 MnS@ZGF Gel exhibits strong adhesion to various biological tissues and abiotic substrates. Rheological results show that (fg), MnS@ZGF Gel has strong adhesion to various biological tissues and abiotic substrates. Figure 2h), within the test range, the storage modulus (G′) of each group of hydrogels was higher than the loss modulus (G″), indicating that a stable network structure dominated by elastic response was successfully constructed, among which MnS@ZGF Gel had a higher gel failure point and storage modulus. Dynamic strain cycling and compression tests further showed that ( Figure 2 i) The hydrogel has good self-healing ability and mechanical stability, and its compressive strength is significantly better than that of the blank control group.

[0036] Example 4: In vitro proliferation and in vivo degradation like Figure 3 The results (ab) show that the scratch assay was used to evaluate the effect of each hydrogel group on the migration behavior of human umbilical vein endothelial cells (HUVECs). The results showed that the scratch gap in the MnS@ZGF Gel treatment group was significantly reduced after 12 h of culture, and the cell migration rate was significantly higher than that of other control groups at 24 h, indicating that it has a good cell migration-promoting effect. This result indicates that MnS@ZGF Gel can promote cell migration through Co... 2+ Mn 2+ The synergistic effect of active components such as H2S promotes endothelial cell migration, thereby facilitating wound angiogenesis and tissue repair. Furthermore, after implantation of IR820-labeled MnS@ZGF Gel into animals, its fluorescence signal gradually weakened within 7 days. Figure 3 c) indicates that the hydrogel can achieve continuous and controllable degradation and absorption in vivo, which is beneficial for early wound coverage and protection as well as safe removal of materials later.

[0037] Example 5: In vitro antibacterial and in vitro / in vivo hemostatic properties The plate count method was used to evaluate the effects of each group of hydrogels on Staphylococcus aureus (Staphylococcus aureus). S. aureus ) and Escherichia coli ( E. coli The antibacterial ability of ) was as follows: Figure 3 As shown in Figure d, FG Gel showed weak inhibitory effects against both bacteria. After the introduction of OSA and PL, the colony-forming units of FOP Gel decreased significantly, indicating that PL endowed the hydrogel with certain endogenous antibacterial activity. Further introduction of MnS@ZG enhanced the antibacterial activity of MnS@ZF Gel and MnS@ZGF Gel, with MnS@ZGF Gel exhibiting the strongest broad-spectrum antibacterial activity under 10 mM glucose conditions. S. aureus and E. coli The sterilization rates were all close to 99%. This result indicates that MnS@ZG can significantly enhance the antibacterial effect of hydrogels by catalyzing the generation of H2O2 and further amplifying the ROS signal in the presence of glucose.

[0038] In addition, such as Figure 3 As shown in Figure e, the in vitro coagulation index (BCI) test indicated that both FOP Gel and MnS@ZGF Gel had significant procoagulant effects, and the BCI value of MnS@ZGF Gel was consistently lower than that of other groups at all time points, indicating that its hemostatic efficiency was higher. Further evaluation of in vivo hemostatic performance was conducted using a liver hemorrhage model. Figure 3 f), the results showed that the untreated group had significant bleeding, while the MnS@ZGF Gel treated group had only a small amount of blood exudation, indicating that the hydrogel has excellent in vivo hemostatic ability.

[0039] Example 5: In vitro antioxidant, anti-inflammatory, and immunomodulatory properties like Figure 4 As shown in Figure a, under H2O2-induced oxidative stress, compared with the control group and the FG Gel group, the green fluorescence signal of L929 cells treated with MnS@ZGFGel was significantly reduced, indicating that it can effectively reduce intracellular ROS levels. Flow cytometry and cell viability experiments further confirmed this. Figure 4 MnS@ZGF Gel exhibits excellent antioxidant capacity, significantly reducing oxidative damage and improving cell survival rate, indicating that it can play a sustained antioxidant and cell-protective role in the wound repair process.

[0040] In addition, such as Figure 4 As shown in Figure e, significant H2S fluorescence signals were detected in cells treated with both MnS@ZF Gel and MnS@ZGF Gel, with the MnS@ZGF Gel group exhibiting the strongest signal. This indicates that the system can continuously release H2S in the pathological microenvironment, thereby helping to alleviate oxidative stress and inflammatory responses.

[0041] Furthermore, after treatment with different hydrogels, the expression of CD86 red fluorescence in macrophages gradually decreased, while the expression of CD206 green fluorescence gradually increased. Figure 4 (d & f). Among them, the MnS@ZGF Gel treatment group showed the lowest CD86 expression and the strongest CD206 expression, indicating that it can significantly inhibit M1 polarization and promote M2 polarization, and has good anti-inflammatory and immunomodulatory effects, which is beneficial to establishing a regenerative microenvironment for the repair of diabetic chronic wounds.

[0042] Example 6: In vivo repair of diabetic infected wounds Constructing a mouse model of full-thickness Staphylococcus aureus infection in diabetic patients, such as... Figure 5 As shown in Figure a, during the observation period, the wound area of ​​each treatment group showed varying degrees of reduction. Figure 5bc). Among them, the MnS@ZGF Gel treatment group consistently showed the fastest wound closure speed; on day 14 of treatment, the wound closure rate in the PBS control group was only about 56%, while the wound closure rate in the MnS@ZGF Gel group reached about 94%, significantly better than the FOP Gel, FG Gel, and commercial Hydrosorb dressing groups, indicating that MnS@ZGF Gel can significantly accelerate the healing process of infected diabetic wounds. Furthermore, during the treatment period ( Figure 5 d) The weight of mice in each group did not change significantly, indicating that the hydrogels in each group had good in vivo safety.

[0043] Furthermore, bacterial agar cultures were performed on the wound tissue on day 3 of treatment. Figure 5 (e) The results showed that the MnS@ZGFGel group had the lowest bacterial load in the wound, with a significant reduction in the number of colonies, and Gram-positive bacteria were almost undetectable in the wound tissue. These results indicate that the hydrogel can significantly reduce the bacterial load in infected wounds through efficient bactericidal action mediated by early ROS and the synergistic antibacterial effect of the matrix itself, providing favorable conditions for subsequent inflammation resolution and tissue repair.

[0044] Further histological analysis of the wound tissue in each group was conducted, such as... Figure 6 As shown in Figure a, H&E staining results indicated that on day 7 of treatment, the PBS group still exhibited significant inflammatory cell infiltration and minimal epidermal regeneration; while the MnS@ZGF Gel group showed the most significant wound contraction, re-epithelialization, and inflammation reduction. Masson staining further revealed that the PBS group had less collagen deposition and a disordered arrangement, while the MnS@ZGF Gel group had a more dense and orderly collagen fiber arrangement, indicating that it can effectively promote extracellular matrix deposition and tissue structure reconstruction.

[0045] Example 7: In vivo anti-inflammatory properties On day 7 of treatment, immunohistochemical and immunofluorescence analyses were performed on inflammation-related markers in the wound tissue. For example... Figure 6 As shown in b, compared with the PBS group, the expression of the pro-inflammatory factor IL-6 in the wound tissue treated with MnS@ZGF Gel was significantly downregulated. Simultaneously, the fluorescence signal of the pro-inflammatory M1 macrophage marker CD86 was significantly weakened, while the fluorescence signal of the anti-inflammatory M2 macrophage marker CD206 was significantly enhanced, indicating that macrophages polarized from M1 to M2 types. These results demonstrate that MnS@ZGF Gel can effectively inhibit the chronic inflammatory response in diabetic infected wounds and establish a repair microenvironment conducive to tissue regeneration through H2S-mediated immune reprogramming.

[0046] Example 8: In vivo angiogenesis-promoting properties Analysis by immunofluorescence staining, such as Figure 6 As shown in Figure c, compared to other treatment groups, the red fluorescence signal of the vascular endothelial-specific marker CD31 was significantly enhanced and more densely distributed in the wound tissue of mice treated with MnS@ZGF Gel, indicating that the construction process of the microvascular network in the wound was accelerated. These results demonstrate that this hydrogel can effectively promote angiogenesis, which is beneficial for further accelerating the repair process of diabetic infected wounds.

Claims

1. A hybrid nanozyme-enhanced adaptive glycopeptide hydrogel dressing, characterized in that, The hydrogel dressing is composed of a hybrid nanoenzyme MnS@ZG and a glycopeptide hydrogel matrix. The hybrid nanozyme MnS@ZG consists of an MnS core and cobalt ions (Co). 2+ It consists of a shell composed of 2-methylimidazole (2-MIM) and glucose oxidase (GOD); The glycopeptide hydrogel matrix is ​​formed by the dynamic Schiff base bond, hydrogen bond and metal coordination of sodium oxidized alginate (OSA), ε-polylysine (PL) and thermosensitive F127.

2. The hydrogel dressing according to claim 1, characterized in that, The MnS@ZG hybrid nanozyme is regularly spherically dispersed and can induce the production of reactive oxygen species (ROS) and hydrogen sulfide (H2S) in vitro.

3. The hydrogel dressing according to claim 1, characterized in that, The hydrogel dressing exhibits fluidity and injectability at low temperatures and can rapidly gel in situ at body temperature. It possesses tissue adhesion, self-repair, mechanical stability, and controllable degradation properties. It also shows an in vitro antibacterial rate of nearly 99% against Staphylococcus aureus and Escherichia coli, and demonstrates good cell proliferation promotion, in vitro and in vivo hemostasis, and in vitro anti-inflammatory and antioxidant properties.

4. A method for preparing a hybrid nanozyme-enhanced adaptive glycopeptide hydrogel dressing according to any one of claims 1-3, characterized in that, Includes the following steps: Step 1: Preparation of MnS nanoparticles; Step 2: Coating Co onto the surface of MnS nanoparticles 2+ / 2-MIM, to prepare MnS@Z nanoparticles; Step 3: Load GOD onto the surface of MnS@Z nanoparticles to obtain MnS@ZG hybrid nanozymes; Step 4: Preparation of oxidized sodium alginate (OSA); Step 5: Mix the MnS@ZG hybrid nanozyme with F127, and further mix it thoroughly with OSA and PL to form a hybrid nanozyme-enhanced glycopeptide hydrogel dressing, namely MnS@ZGF Gel.

5. The preparation method according to claim 4, characterized in that, In step 1, MnS nanoparticles are prepared by a solvothermal method at a reaction temperature of 190°C and a reaction time of 4 h.

6. The preparation method according to claim 4, characterized in that, In step 4, OSA is prepared by reacting sodium alginate with sodium periodate. After the reaction is completed, the reaction is terminated with ethylene glycol, purified by dialysis, and then freeze-dried.

7. The preparation method according to claim 4, characterized in that, In step 5, F127 was mixed with MnS@ZG hybrid nanozyme at 4℃ to form a homogeneous solution, then OSA solution and PL solution were added and mixed evenly, and incubated at 37℃ for 1h to form MnS@ZGF Gel.

8. The use of the hydrogel dressing according to any one of claims 1-3 in the preparation of diabetic chronic wound repair dressings, infectious wound repair dressings, antibacterial and anti-inflammatory wound dressings, or tissue regeneration promoting dressings.

9. The application according to claim 8, characterized in that, The hydrogel dressing achieves synergistic repair of diabetic infected wounds by locally lowering blood sugar, amplifying ROS signals for sterilization, continuously releasing H2S, inhibiting chronic inflammation, inducing macrophage M2 polarization, promoting angiogenesis and orderly collagen deposition.